Dithienothiophene‐Based Triphenylamine‐Containing Branched Copolymers for Electrochromic Applications. Issue 8 (24th June 2015) - Cho, Ching Mui; Neo, Wei Teng; Ye, Qun; Lu, Xuehong; Xu, Jianwei
Abstract A series of dithienothiophene‐based electrochromic polymers are synthesized by a Stille coupling reaction of 2, 6‐bis(trimethylstannyl)dithieno[3, 2‐b:2′, 3′‐d]thiophene, 2, 5‐dibromo‐3, 4‐bis(dodecyloxy)thiophene, and tris(4‐bromophenylamine). The resulting polymers have high molecular weights in the range of 59 200 to 81 300 g mol−1, and good solubility in common organic solvents. The polymer films are purple/red in neutral states and gradually become gray when oxidized to an intermediate state and blue when fully oxidized. Incorporation of triphenylamine into the polymer chains has resulted in a significant increase in the redox stability, which renders this a potential method to create high‐performance electrochromic polymers.